External Quality Assessment Schemes in Pathology in Portugal (PNAEQ-Labquality) 2013-2014 - Correia, Helena (2016)
Since 2001, the Portuguese external quality assessment program (PNAEQ) has been working with Labquality and a consortium of Investigation and Development was established in 2013. In 2009, the Histopathology and Immunochemistry schemes were the first programs available in the area of Pathology. Clinical cytology and Technology schemes were introduced during the following years. Initially, the number of participants was very low. Knowing that participation on EQAs programs allows monitoring of the laboratories’ performance it was necessary to invest in the education of laboratory personnel to insure the competence of the laboratory’s technicians and their ability to provide reliable and accurate results. PNAEQ and Labquality and their Pathology Experts made efforts promoting awareness of these programs by organizing meetings in 2014 and 2015, for all the Portuguese Pathology laboratories with the collaboration of the College of Portuguese Pathologists. These meetings were very successful since almost all of the 37 Portuguese pathology laboratories participated and a total of 41 participants were present. The agenda was about the importance of Quality Control in general, EQA schemes as a way to compare one’s own results with those of piers and finally to distribute information about the requirements for the accreditation of pathology laboratories.